Predictors for a Cure Rate of Severe Acute Malnutrition 6-59 Month Children in Stabilizing Center at Pawe General Hospital, Northwest Ethiopia: Retrospective Cohort Study - Kebede, Fassikaw; Eticha, Nemera; Negese, Belete; Giza, Mastewal; Tolossa, Tadesse; Wakuma, Bizuneh (International Journal of Child Health and Nutrition, 2021)
Malnutrition (over and undernutrition) is a major public health problem across the globe, especially undernutrition is responsible for one-third of the death of children in underprivileged populations. Each year more than 25 to 35 million under-five children have suffered from Severe Acute Malnutrition (SAM). The sub-Saharan African countries account for the lion's share of this case fatality rate. The case in Ethiopia is not different from other countries. This study's main aim is to assess predictors for the cure rate of Severe Acute Malnutrition in 6-59 month Children in stabilizing center at Pawe General Hospital, Northwest Ethiopia. A retrospective cohort study. Methods: Hospital-based retrospective cohort study was employed among 454 admitted under-five SAM children from Januarys1st 2015-to December 30, 2019. Data were cleaned, coded, and entered into Epi-Data 3.1; then exported to STATA/SE- 14/R for analysis. Survival analysis was used to check each variable's proportional hazard assumption and no variable Schoenfield test <0.05. Variable with AHR at 95 % CI at P-value less than 0.05 considered as significant. Final model adequacy was checked by Nelson Alana and Cox Snell residual plot test. Result: Totally 454 (90.4%) individual data were included for final analysis; Sixty-five percent of 65.4% (95%CI: 50.1- 69.2) admitted children declared as cured, 16.52 % of them defaulted and 11.5% of children reported as dead. The median age and median cure time of SAM children were found at 2.2 years and 13 days (±7), respectively. Children diagnosed marasmus (AHR=1.56: 95% CI 1.08--2.2, p<0.018), with No nasal-gastric intubation (NGT) during admission (AHR= 1.31: 95%CI (1.04 --1.67, P<0.029) and taking F-100 milk (AHR=5.42 95% CI (2.92--9.85, p<0.001) were associated with treatment cure rate. The conclusions: The overall treatment cure rate of this study was remaining low at 65.4% compared to the sphere standard sets reference (i.e., >75-77.9 %). Concerning associated factors addressing F-100 milk, making SAM under-five children with no NGT and increased treatment cure rate was independently associated with treatment cure rate.